El inconsciente teclado: la máquina de escribir en los idiomas inventados de Cortázar - Juan Cristóbal Castro (Cuadernos LIRICO)
This article concerns the origins of Cortázar's imaginary languages as a resullt of the use of the typewriter. Following the proposals of some theorists (Kittler, Mcluhan, Olson), as well as the works and personal letters of the Argentine writer, I would like to construct the tentative line of influence that led him to think about some of his fictional languages.